Site of Nerve Division Affects Pain-Related Behavior and Spinal Cord Glial Proliferation after C7 Neurotomy in a Rat Stroke Model - Zhenpeng Li; Jintao Fang; Jiantao Yang; Bengang Qin; Wenting He; Jian Qi; Qingtang Zhu; Honggang Wang; Liqiang Gu (Pain Research and Management)
Objective. This study aimed to evaluate whether the site of C7 neurotomy affects spinal cord glial cell activation and pain-related behavior on the paralyzed side in a rat stroke model. Methods. After middle cerebral artery occlusion (MCAO) was induced in male Sprague-Dawley rats, they underwent C7 neurotomy 0, 2, and 4 mm distal to the intervertebral foramen on the paralyzed side. Pain-related behavior and immunofluorescence examination of spinal cord glial cell activation in the ipsilateral C7 dorsal horn were evaluated. Results. Mechanical paw withdrawal threshold (MPWT) was lower, and the number of microglia and astrocytes (/mm2) was higher as the distance between the site of C7 neurotomy and the intervertebral foramen decreased from 4 mm to 0. Conclusion. The site of C7 neurotomy affects MPWT and spinal cord glial proliferation in rats with MCAO. Nerve division closer to intervertebral foramen resulted in lower MPWT and higher degree of glial proliferation in the spinal cord.